The practice of physical activity in times of pandemic COVID-19 in the Federal Institute of Maranhão (IFMA): awareness campaign (Research, Society and Development, 2022)
This article aimed to present concepts and examples of awareness campaigns of the practice of Physical Activity (PA) developed by the Federal Institute of Education, Science and Technology of Maranhão (IFMA), and to highlight the influence of PA in combating COVID-19. It is an exploratory and descriptive qualitative research based on a bibliographic survey, with access to the set of electronic materials on AF and COVID-19. As a result, it is highlighted that knowledge of reality is the basic process in the awareness process and one of the most effective means to stimulate the development of critical awareness is awareness campaigns. In this sense, the awareness campaigns on PA practice developed at IFMA show the influence and importance of PA in combating the new coronavirus. It is concluded that sensitize and raising awareness are arduous tasks on issues related to human behavior and are important tools for obtaining results, that is, they are significant elements to positively cooperate with the quality of life.